Digital Communication Strategy of Instagram Account @hakimbicara as Public Speaking Education Media - Trianuri, Lintang; Apriliani, Riski (Jogjakarta Communication Conference (JCC), 2025)
The @hakimbicara account is an Instagram social media account that focuses on delivering public speaking education messages. This research discusses the digital communication strategy carried out by @hakimbicara to deliver public speaking education messages on Instagram social media. The purpose of this research is to find out how the digital communication strategy carried out by @hakimbicara account in delivering educational information and to find out the application of The Circular Model of SOME theory in the communication process. This research uses descriptive qualitative methods and applies an interpretative paradigm. This research uses the theory of The Circular Model of SOME popularized by Regina Luttrell which consists of share, optimize, manage, engage. This research uses online and offline interview methods with sources from the account owner of @hakimbicara and three of his followers. Based on the results and discussion of research, Instagram social media @hakimbicara is very impactful for the followers to improve public speaking skills and get positive feedback from the audience. Besides that, success, there are obstacles and challenges faced by @hakimbicara account in delivering this public speaking education content.